Heated tobacco products: another tobacco industry global strategy to slow progress in tobacco control. (12th September 2018) - Bialous, Stella A; Glantz, Stanton A
Abstract : There has been a global decline in tobacco consumption that, if continued, will negatively impact the tobacco industry's profits. This decline led the industry to invent and market new products, including heated tobacco products (HTP). HTP are an extension of the industry's strategies to undermine government's tobacco regulatory efforts as they are being promoted as part of the solution for the tobacco epidemic. Under the moniker of 'harm reduction', the tobacco companies are attempting to rehabilitate their reputation so they can more effectively influence governments to roll back existing tobacco control policies or create exemptions for their HTP. Rolling back tobacco control policies will make it easier for the companies to renormalise tobacco use to increase social acceptability for all their products. When regulations are absent or when loopholes exist in classifying HTP as a tobacco product (thus subject to all tobacco control regulations), the industry's marketing of HTP is making these products more visible to the public and more accessible. Governments need to ensure that HTP are regulated as tobacco products or drugs and reject partnerships with the tobacco companies to promote 'harm reduction'. The tobacco companies remain the vector of the tobacco-caused epidemic and cannot be part of the global tobacco control solution.